Tang’s method is an effective new treatment for anterior shoulder dislocation - Peng Yuan; Ruixin Tang; Ye Zhou; Lutian Liao; Sijun Ren; Miao Tang (Scientific Reports)
Abstract The principal aim of this study was to present a novel approach to manipulative repositioning for the management of anterior shoulder dislocation. This was evaluated in comparison with the established repositioning method to ascertain its clinical efficacy. Seventy-six patients with anterior dislocation of the shoulder joint were randomly assigned to one of two groups. Each group underwent reducing using either Tang’s method or Hippocrates’ method, respectively. The patients were then monitored for six months. The researchers analyzed and compared the general condition, reduction time, reduction success rate, VAS score, and ASES score of the patients in the two groups. No statistically significant difference was observed in the general condition of the patients prior to the reduction between the two groups. The mean reduction time for the Tang’s method group (70.9 ± 11.88) was found to be significantly shorter than that observed for the Hippocrates method group (411.6 ± 50.41). The reduction success rate was significantly higher in the Tang’s method group (100.00%) than in the Hippocrates method group (80.56%). No statistically significant difference was observed in VAS scores between the two groups prior to the reduction. However, the Tang’s method group demonstrated superior outcomes compared to the Hippocrates method group during and following the reduction. No statistically significant difference was observed in ASES scores between the two groups prior to the reduction. However, at one, three, and six months post-reduction, the Tang’s method group exhibited significantly superior outcomes compared to the Hippocrates method group. The Tang’s method is a safe and effective method of reducing for anterior dislocation of the shoulder. It is significantly superior to the traditional Hippocrates method.